Estrategia metodológica inclusiva y su incidencia en el proceso de enseñanza-aprendizaje de los estudiantes con necesidades educativas especiales intelectual lingüística de 5to año de educación básica de la Escuela Gabriel García Moreno de la parroquia Ricaurte, cantón Urdaneta, Provincia Los Ríos - Jacome Sotomayor, Yulia Maricela (2019)
The titling work called: "METHODOLOGICAL STRATEGIES TO IMPROVE THE TEACHING LEARNING PROCESS IN THE BASIC AVERAGE OF THE PLURIDOCENT EDUCATIONAL UNIT" EL PROGRESO ", LEADING PERIOD 2016-2017", has as its specific purpose: to propose inclusive methodological strategies to promote and accompany in a better way the teaching learning system in our object of study. The objective pursued by this methodological proposal, is to improve a pedagogical situation is that teachers use a variety of methodological strategies within their training to achieve meaningful learning in their recipients. The problem that gave rise to the elaboration of this methodological proposal are the inferior performances in the students as a result of the use of traditional methodological strategies by the teachers, hindering the authentic development of the skills with performance criteria. The methodology used for the elaboration of the methodological proposal starts from the analysis of the academic performance of the middle school students, of our object of study, to then apply scientific research techniques to collect information, including: observation, surveys and to support the theory that bases the methodological proposal we turn to bibliographical and electronic research based on the objectives set. As results, it is determined that teachers of our study object must use several methodological strategies in the teaching-learning process, such as: problem-based learning, conceptual maps, mental maps, timelines and Venn diagrams to arouse interest in students and promote meaningful learning.